Globalisation in Crisis? - ZG Überblick (Wirtschaftsdienst)
Abstract Globalisation has lost considerable speed in the last decade. World trade grew more slowly than world production in the 2010s. Protectionist tendencies are slowing down world trade, even if multilateralism has regained support in the post-Trump presidency era. The coronavirus pandemic and supply bottlenecks have also thrown sand into the gears of globalisation. Only international trade in services is still showing robust growth. Germany’s close economic ties with the world also mean that disruptions in supply chains or slumps in demand during pandemics are to be viewed extremely negatively and appropriate strategies for global health security should be pursued.